From podium to leadership: Examining the influence of demographics, peak Olympic achievement, and career tenure on athlete leadership - Zaharia, Noemi; Zaharia, Valentin Cristian (Journal of Sports Research, 2025)
This study examines how demographic and performance-related factors influence perceived leadership traits among Olympians, contributing to an understanding of leadership identity shaped by elite sport experience. Responses from 242 Olympians representing 67 countries and 44 Olympic sports were analyzed using the Leadership Trait Questionnaire (LTQ) to assess self-reported leadership characteristics. The study focused on gender, age, highest Olympic placement, and number of Olympic participations. Results show that all four variables significantly affect leadership self-perception, with gender and achievement level showing particularly notable differences. These findings suggest that leadership development in elite athletes is influenced not only by competitive success but also by broader experiential and demographic factors. The study offers a cross-national perspective on athlete leadership, revealing diverse leadership profiles within the Olympic community. Practical implications include the integration of leadership training into athlete development and career transition programs, emphasizing the transferable value of Olympic experience beyond sport. By identifying key influences on leadership self-perception, the research supports a more holistic approach to athlete identity and post-sport career readiness. The study provides a foundation for future research on leadership development in sport and its relevance to broader professional contexts.